A SYSTEMATIC LITERATURE REVIEW OF LINE BALANCING PRACTICES IN INDUSTRY: A REVIEW AND TRENDS - Saerang, Christwandy Roland; Pratama, Bagus Wahyu Nur; Lukito, Tito; Purba, Humiras Hardi (Universitas Putera Batam, 2025)
The competition in the evolving industry to improve optimal production line efficiency is becoming increasingly intense. Every industry focuses on reducing waste, enhancing productivity, and utilizing resources more effectively. Line balancing is one of the techniques from lean manufacturing that addresses obstacles to improving productivity performance. Therefore, the aim of this paper is to review the application and trends of the line balancing method in the industrial sector, particularly in manufacturing companies worldwide. The findings from a review of 40 journals on line balancing, including case studies in the industry and literature reviews, show that the success of implementing line balancing depends on key factors that optimize productivity and process flow efficiency. Thus, line balancing is highly beneficial when applied in an industry and is crucial to integrate with emerging technologies, which are expected to bring significant changes to the industry.